Do work placements improve final year academic performance or do high-calibre students choose to do work placements?. Issue 6 (3rd June 2017) - Jones, C.M.; Green, J.P.; Higson, H.E.
Abstract : This study investigates whether the completion of an optional sandwich work placement enhances student performance in final year examinations. Using Propensity Score Matching, our analysis departs from the literature by controlling for self-selection. Previous studies may have overestimated the impact of sandwich work placements on performance because it might be the case that high-calibre students choose to go on placement. Our results, utilising a large student data set, indicate that self-selection is present, but the effects of a placement on student performance still have an impact. This robust finding is found to be of a remarkably similar magnitude across two UK universities.